Absence of routine molecular testing and prevalence of HIV-2 infection in regions hardest-hit by HIV infection - Forbi, Joseph C; Esona, Mathew D; Iperepolu, Hellen O; Adoga, Moses P; Agwale, Simon M (The Journal of Infection in Developing Countries, 2012)
Introduction: Investigating the incidence and dynamics of HIV-2 and false-negative HIV test results in a highly sexually active population where frequent opportunities exist for acquiring and transmitting infections provides additional understanding of the epidemiology of the virus in Africa. Methodology: The HIV status of 900 active female sex workers (FSWs) was determined using two lateral flow rapid assays in series. The second rapid test device incorporates type-specific recombinant peptides that discriminate between HIV-1 and HIV-2 infection. HIV sero-negative samples were re-tested for HIV infection and their viral loads determined using the NucliSENS real-time nucleic acid sequence-based amplification (NASBA) platform. Results: In total, 335 FSWs were determined to be HIV positive, the majority (227; 67.8%) of whom were between the ages of 20 and 30 years. Eighteen (5.4%) were found to have evidence of HIV-2 infection, 17 of whom were co-infected with HIV-1. Only one HIV-2 mono-infection was observed. Out of 565 HIV-negative individuals determined by serology, 11(1.9%; p>0.05) were found to be HIV-1 positive when tested via the NASBA platform. Conclusion: False negative test results, HIV-2 infection, and complex transmission networks among FSWs may aid in fueling the HIV epidemic in the Nigerian population. These findings demonstrate the need to reevaluate the quality of HIV serological diagnostics, control services, and stress the need for widespread introduction of molecular testing among high-risk populations in the country.